2021
DOI: 10.26434/chemrxiv.14579259.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Situ Probing Potassium-ion Intercalation-induced Amorphization in Crystalline Iron Phosphate Cathode Materials

Abstract: <p>Na-ion and K-ion batteries are promising alternatives for large-scale energy storage applications due to their abundancy and lower cost. However, designing an electrode structure to reversibly accommodate these large alkali-ions is the remaining challenge before their commercialization. Intercalation of these large ions could cause irreversible structural deformations and amorphization in the crystalline electrodes. The designing of new amorphous electrodes is another route to develop electrodes to s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Composite electrodes were prepared by mixing pristine lithium iron phosphate (LiFePO 4 , LFP, Hanwha Chemical) with sodium carboxymethyl cellulose (binder, CMC, Aldrich) and conductive additive (carbon black, Alfa Aesar) in 8:1:1 mass ratio. Iron phosphate (FePO 4 , FP) composite electrode was formed by electrochemical displacement technique using a pristine LFP composite electrode [21][22][23][24] via galvanostatic cycle at a rate of C/ the composite electrode were used as a speckle pattern suitable for the calculations of displacement fields and their resultant strain distribution on the electrode surface.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Composite electrodes were prepared by mixing pristine lithium iron phosphate (LiFePO 4 , LFP, Hanwha Chemical) with sodium carboxymethyl cellulose (binder, CMC, Aldrich) and conductive additive (carbon black, Alfa Aesar) in 8:1:1 mass ratio. Iron phosphate (FePO 4 , FP) composite electrode was formed by electrochemical displacement technique using a pristine LFP composite electrode [21][22][23][24] via galvanostatic cycle at a rate of C/ the composite electrode were used as a speckle pattern suitable for the calculations of displacement fields and their resultant strain distribution on the electrode surface.…”
Section: Methodsmentioning
confidence: 99%
“…[26] A recent in situ XRD study also demonstrated the amorphization of the crystalline iron phosphate during the intercalation of K ions. [21] The corresponding electrochemical strains in the electrodes upon Li, Na, and K intercalation are shown in respectively. K ions were only able to intercalate into electrode structure up to an SOD of ca.…”
Section: First Cyclementioning
confidence: 99%
See 3 more Smart Citations